Victorian Contexts - Roston, Murray. author. aut Link
VIII, 255 p.
Keywords: Examines how both artist and writer in the Victorian era responded to the shared challenges, assumptions, and dilemmas of their time, often unaware that the same problems were being confronted in the kindred media. The placing of such writers as Dickens, G.Eliot, Hopkins, and Henry James within the context of Victorian painting, architecture, and interior design offers fresh insights into their works, as well as reassessments of such themes as the mid-century representation of the Fallen Woman or the impact of commodity culture upon contemporary aesthetic standards.